(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2023)
This article explores the imperative of judicious water usage amidst the complex and evolving global conditions. It emphasizes the significance of responsible water management in the face of growing population pressures, climate change, and the need for sustainable development. By delving into the multifaceted aspects of water use, this article underscores the importance of efficient practices, conservation, and equitable distribution to ensure a secure and resilient future for all.